2013
DOI: 10.1007/s10493-013-9729-z
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative and quantitative study of mites in similar alfalfa fields in Greece

Abstract: The present study investigated the mite fauna and the relative abundance of mites present in foliage and litter of two adjacent and similar alfalfa fields, differing only in the number of cuttings, in Kopais Valley (Central Greece) through 2008-2010. We also examined the relationship between assemblage patterns of Mesostigmata, Oribatida and Prostigmata by comparing their population fluctuation, population density, species richness and diversity. Spatial distribution of common dominant and influent mite specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 30 publications
2
14
0
2
Order By: Relevance
“…Fan and Zhang (2007) reported that this species had been found in association with a broad range of plant and animal material in a variety of habitats. Recently, Badieritakis et al (2012Badieritakis et al ( , 2014 recorded it from both the foliage and litter of Medicago species in Greece. These reports, however, are descriptive and observational in nature, although feeding of T. curvipenis on various plants, fungi and stored food is assumed, based on knowledge of related species of Tyrophagus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fan and Zhang (2007) reported that this species had been found in association with a broad range of plant and animal material in a variety of habitats. Recently, Badieritakis et al (2012Badieritakis et al ( , 2014 recorded it from both the foliage and litter of Medicago species in Greece. These reports, however, are descriptive and observational in nature, although feeding of T. curvipenis on various plants, fungi and stored food is assumed, based on knowledge of related species of Tyrophagus.…”
Section: Discussionmentioning
confidence: 99%
“…In their monograph on Tyrophagus, Fan and Zhang (2007) reported this species in association with many plant and animal hosts in a very broad range of habitats in Australia, France, Portugal and New Zealand. Badieritakis et al (2012Badieritakis et al ( , 2014 recently recorded this species in foliage and litter of Medicago species in Greece. However, virtually nothing else is known about the life history and biology of this species.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the economic importance of this crop in Greek agriculture, little is known about the mite fauna of alfalfa in Greece. In this respect, Badieritakis et al (2014) contributed with results regarding qualitative and quantitative information over mite assemblages of foliage and litter mites of two considerably similar and non-pesticide treated alfalfa hay fi elds in Central Greece, which only diff ered in the number of cuttings. In that study we found that the population fl uctuation of mites in the foliage of both fi elds was similar, unlike that of litter.…”
Section: Introductionmentioning
confidence: 95%
“…Based on these fi ndings (Badieritakis et al, 2014), the present work has as main objective to compare the mite fauna as well as the relative abundance of mites in the foliage and litter of a bifenthrin-treated alfalfa hay fi eld located in the same area (approximately 100 meters away) with the non-pesticide treated fi elds as well as the species richness, diversity and spatial distribution of mites in the foliage and litter.…”
Section: Introductionmentioning
confidence: 99%
“…Cunaxids occur in most terrestrial habitats, including soil and leaf litter (Den Heyer 1977a, Luxton 1982; Javan et al 2012); moss and lichen (Sepasgosarian 1984, Tseng 1980); on vegetation (Miller 1925, Swift and Goff 2001, Ferla and Moraes 2002) including coniferous trees (Lehman 1982), tropical trees (Castro and Moraes 2007) including guava trees (Mallikarjunappa and Nageshchandra 1990), Ferla and Moraes 2002), mango trees (Mohamed et al 2014), coconut trees (Mariau and Biggins 2001; da Silva et al 2014), and rubber trees (Hernandes and Feres 2006), ornamental plants (Tagore and Putatunda 2003), invasive weeds (Walter 1999), agricultural plants such as citrus trees (Muma 1960, Olivier 1968, Ramsey et al 1972a, Soliman and Mahfood 1978, Vacante and Nucifora 1986, Quilici et al 1997, Grout and Ueckermann 1999, Ferla and Moraes 2002, Fadamiro et al 2009), deciduous fruit trees (Nesbitt 1946, Garman 1948, Lord 1949, Ramsey et al 1972b, Quilici et al 1997, Ferla and Moraes 1998, Ferla and Moraes 2002; Shakhsi Zare et al 2012), cotton (Kuznetzov and Sizova 1978), strawberries (Ferla et al 2007), grape vineyards (Schruft 1971, Jubb et al 1985, Molnar 1997), alfalfa fields (Badieritakis et al 2014), and plants in urban settings (Lahiri et al 2004); vertebrate nests (Garman 1948, Gupta and Chattopadhyay 1978, Gupta and Paul 1985, Estebanes-Gonzales 1997); caves (Cooreman 1954, Turk 1972, Zacharda 1978); animal debris (Corpuz Raros et al 1988, Taha et al 1988); tree holes (Atyeo 1958, Lin and Zhang 2002); house dust (Oliveria and Daemon 2003); and stored food products (Huges 1976, Tseng 1980, Fan 1992). Individual species, however, are thought to be restricted to a particular habitat.…”
Section: Introductionmentioning
confidence: 99%